INVESTIGASI PENGARUH KONDISI LALU LINTAS DAN ASPEK METEOROLOGI TERHADAP KONSENTRASI PENCEMAR SO2 DI KOTA SEMARANG - Istirokhatun, Titik; Agustini, Ita Tetriana; Sudarno, Sudarno (Universitas Diponegoro, 2016)
The presence of air pollution in ambient air is closely related to the incidence of adverse reactions affecting human health. One of harmful pollutants and potentially major cause health problems is sulfur dioxide (SO 2 ). The number of vehicles that are passing and queuing on the crossroads because of traffic light can affect the concentration of SO 2 . Besides, in these locations there are a lot of road users which are potentially exposed by contaminants, so information about the concentration of SO 2 is important to know. This study aimed to investigate the impact of meteorological factors and the number of vehicles on SO 2 concentrations. Impinger was used for air sampling, and pararosaniline method was used for determining SO 2 concentration. Sampling and calculation of the number of passing vehicles were performed 3 times ie in the morning, afternoon and evening. Based on the results of the study, the highest concentrations of SO 2 were on the range of 15-21 mg/Nm3.